Nanoparticles for crop improvement and management - Das R.; Kumar P.; Agrawal S.; Singh K.; Singh N.; Singh S.; Vishwakarma J.; Rajput V.D.; Singh A.K.; Minkina T.M.; Bhattacharya I.; Mishra S.K.; Tiwari K.N. (My University, 2025)
Agriculture is the mainstay, especially for developing countries. Climate changes globally and a rapidly expanding population are posing new challenges to food security, necessitating effective crop enhancement technologies that provide excellent crop quality and quantity. Chemicals such as pesticides and fertilizers are commonly used to address biotic stressors in crop production, but these have serious consequences for crop quality and health. Nanotechnology is a novel and scientific method employed in designing, manipulating, and developing beneficial nanoparticles. Materials of nanometer-scale sizes that range from 1 nm to 100 nm are produced using nanotechnology. Due to their small sizes, they have a higher surface area-to-volume ratio (as compared to bulk forms), thereby conferring unique and desirable physical traits. The nanotechnology application in agriculture is outstandingly advancing in order to improve food quality, minimize agricultural inputs, boost nutritional content, and extend shelf life. Crop improvement, crop growth, crop protection, soil enhancement, stress tolerance, and precision farming all benefit from nanotechnology. Nanomaterials provide a platform for delivering agrochemicals and other macromolecules required for plant growth improvement and stress tolerance. Smart agrochemical delivery boosts production by regulating nutrients and water requirements. Both the quality and quantity of agriculture can be improved by using nanoparticles to transform genes and supply macromolecules that encourage expression of genes. The motive of the chapter is to highlight importance of different nanoparticles in abiotic stress, detection of pathogen, seed germination, crop growth, quality enrichment, and supplementation of macronutrients and micronutrients. © 2024 Walter de Gruyter GmbH, Berlin/Boston. All rights reserved.